Interleukin-18 Increases TLR4 and Mannose Receptor Expression and Modulates Cytokine Production in Human Monocytes - Luciane Alarcão Dias-Melicio; Reginaldo Keller Fernandes; Daniela Ramos Rodrigues; Marjorie Assis Golim; Angela Maria Victoriano Campos Soares (Mediators of Inflammation)
Interleukin-18 is a proinflammatory cytokine belonging to the interleukin-1 family of cytokines. This cytokine exerts many unique biological and immunological effects. To explore the role of IL-18 in inflammatory innate immune responses, we investigated its impact on expression of two toll-like receptors (TLR2 and TLR4) and mannose receptor (MR) by human peripheral blood monocytes and its effect on TNF-α, IL-12, IL-15, and IL-10 production. Monocytes from healthy donors were stimulated or not with IL-18 for 18 h, and then the TLR2, TLR4, and MR expression and intracellular TNF-α, IL-12, and IL-10 production were assessed by flow cytometry and the levels of TNF-α, IL-12, IL-15, and IL-10 in culture supernatants were measured by ELISA. IL-18 treatment was able to increase TLR4 and MR expression by monocytes. The production of TNF-α and IL-10 was also increased by cytokine treatment. However, IL-18 was unable to induce neither IL-12 nor IL-15 production by these cells. Taken together, these results show an important role of IL-18 on the early phase of inflammatory response by promoting the expression of some pattern recognition receptors (PRRs) that are important during the microbe recognition phase and by inducing some important cytokines such as TNF-α and IL-10.